Premio Belle Lettere Award. - Buffa, Carlo; Ingmire, Thomas; Massironi, Manfredo; Santi, Tiziano (Mestrino : Edizioni Centrooffset, 1997)
Ingmire, Thomas ; Admas, Keith ; Beney, Hazel ; Dengo, Monica ; Dunham, Ward ; Lundquist, Linnea ; Folsom, Rose ; Hazeldine, Gillian ; Jacobsen, Cheryl ; Kilian, Hermann ; Macchini, Milean Gisella ; Morris, Polly ; Pieper, Katharina ; Schneider, Werner ; Shaw, Paul ; Skarsgard, Susan ; Vian, Sara ; Hanane, Franca ; Allison, Patricia ; Bull, Olive ; Hansen, Kennedy ; Roald, Jan ; Tonetto, Maura ; Brown, Denis ; de Carli, Jill Carlson ; Cornil, Lieve ; Dill, Jane ; Epstein, Glen ; Fragogna, Barbara ; Greenwood, Georgianna ; Jacobsen, Cheryl ; Leavitt, Nancy ; Neuenschwander, Brody ; Owen, Jan ; Dengo, Monica ; Greenwood, Georgianna ; Kolle, Torsten ; Ladurner, Helga ; McNicholas, Kathy ; Morris, Polly ; Schenk, Andreas ; Schilling, Sandra ; Serena, Cristina ; Dunstone, Teresa ; Gamba, Ruggero ; Geffert, Gerald ; Gintole, Julian George ; Grazzani, Lorenzo ; Gripari, Bruno ; Hiemann, Michael ; Laurentii, Lars Olof ; Donald, Megan Mc ; Schilling, Sandra ; Slekyté, Ieva ; Brombin, Piero ; Gamba, Ruggero ; Marcolongo, Paolo ; Neuenschwander, Brody ; Rigo, Floriana
Engels & Italiaans
boek